Patient-centric performance and interpretation of positron emission tomography /computed tomography myocardial perfusion imaging: a clinical consensus statement of the European Association of Cardiovascular Imaging of the European Society of Cardiology - Abadie, Bryan; Liga, Riccardo; Buechel, Ronny R.; Giannopoulos, Andreas A.; Pizzi, María Nazarena; Roque, Albert; Geronazzo, Ricardo; Hyafil, Fabien; Knuuti, Juhani; Saraste, Antti; Slart, Riemer H. J. A.; Cremer, Paul; et al. (Oxford University Press (OUP), 2026)
Positron emission tomography (PET) is the most advanced myocardial perfusion (MPI) technique for the non-invasive assessment of coronary artery disease and its many manifestations, including ischaemia, hibernation, and scar. This comprehensive overview aims to empower clinicians, technicians, and patients with clear, structured knowledge on performing and interpreting PET MPI. This document will describe stress protocols, patient preparation, tracer pharmacodynamics and nuclear properties, camera capabilities, post-acquisition processing, and a comprehensive and clear reporting system for both perfusion and viability imaging.